Malonate Promotes Adult Cardiomyocyte Proliferation and Heart Regeneration. Issue 20 (18th May 2021) - Bae, Jiyoung; Salamon, Rebecca J.; Brandt, Emma B.; Paltzer, Wyatt G.; Zhang, Ziheng; Britt, Emily C.; Hacker, Timothy A.; Fan, Jing; Mahmoud, Ahmed I.
Abstract : Background: Neonatal mouse cardiomyocytes undergo a metabolic switch from glycolysis to oxidative phosphorylation, which results in a significant increase in reactive oxygen species production that induces DNA damage. These cellular changes contribute to cardiomyocyte cell cycle exit and loss of the capacity for cardiac regeneration. The mechanisms that regulate this metabolic switch and the increase in reactive oxygen species production have been relatively unexplored. Current evidence suggests that elevated reactive oxygen species production in ischemic tissues occurs as a result of accumulation of the mitochondrial metabolite succinate during ischemia via succinate dehydrogenase (SDH), and this succinate is rapidly oxidized at reperfusion. Mutations in SDH in familial cancer syndromes have been demonstrated to promote a metabolic shift into glycolytic metabolism, suggesting a potential role for SDH in regulating cellular metabolism. Whether succinate and SDH regulate cardiomyocyte cell cycle activity and the cardiac metabolic state remains unclear. Methods: Here, we investigated the role of succinate and SDH inhibition in regulation of postnatal cardiomyocyte cell cycle activity and heart regeneration. Results: Our results demonstrate that injection of succinate into neonatal mice results in inhibition of cardiomyocyte proliferation and regeneration. Our evidence also shows that inhibition of SDH by malonate treatment after birth extends the window of cardiomyocyte proliferation and regeneration in juvenile mice. Remarkably, extending malonate treatment to the adult mouse heart after myocardial infarction injury results in a robust regenerative response within 4 weeks after injury via promoting adult cardiomyocyte proliferation and revascularization. Our metabolite analysis after SDH inhibition by malonate induces dynamic changes in adult cardiac metabolism. Conclusions: Inhibition of SDH by malonate promotes adult cardiomyocyte proliferation, revascularization, and heart regeneration via metabolic reprogramming. These findings support a potentially important new therapeutic approach for human heart failure. Abstract : Supplemental Digital Content is available in the text.